(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2023)
Yemen, as it is known, is an agricultural country, and it has been called Happy Yemen since ancient times because its people are busy with agriculture and farming. Its poets and wise men praised their dependence on agriculture and their ability to confront hunger and poverty. Among the goals of sustainable development are improving the quality of the environment and the natural resource base on which the agricultural economy depends, preserving the viability of the field economy, and improving the quality of life of farmers and society as a whole. Considering these facts, this paper will work on studying the poetry of the poet Mutahar Al Eryani, which urged agriculture and farming as a source of livelihood, combating poverty and hunger, and decent living, with the goals of sustainable development, which urged agriculture as a means to combat poverty and destitution. Despite our differences with his extremist political orientations, this does not prevent us from praising his agricultural poems, which called for love of the land and concern for agriculture as a basic resource for living in dignity and bliss.